2022
DOI: 10.1111/pace.14500
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between local impedance drop and catheter contact in clinical pulmonary vein isolation use

Abstract: Introduction Local impedance (LI) drop during radiofrequency (RF) application is monitored to assess the lesion formation. Recently, a novel ablation catheter has been introduced to clinical setting, which is capable of monitoring LI and catheter contact parameters including contact force (CF) and contact angle (CA). This study aimed to clarify the correlation between LI drop and catheter contact parameters. Methods and results This prospective study included 15 paroxysmal atrial fibrillation (AF) patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Reconduction over previous linear or substrate ablation and development of new low voltage areas are frequent findings during repeat AF ablation, while persistent conduction blocks have been reported to be present in only 21% using conventional ablation setups (Huo et al, 2020). Therefore, index and repeat ablation procedures as well as ablation within healthy compared to impaired myocardium need to be distinguished when evaluating LI and CF dynamics: In our analysis, baseline LI was lower compared to previous results on index AF procedures, but LI correlated better with ΔLI compared to CF which is in line with published data (Szegedi et al, 2021;Ikenouchi et al, 2022;Solimene et al, 2022;Yasumoto et al, 2022). Furthermore, baseline LI was lower compared to blood pool LI in 45% of RFC applications, whereas an elevation of tissue baseline LI beyond blood pool LI was observed in index AF procedures (Solimene et al, 2022).…”
Section: Value Of Combined Force and Impedance Assessment During Repe...supporting
confidence: 90%
See 1 more Smart Citation
“…Reconduction over previous linear or substrate ablation and development of new low voltage areas are frequent findings during repeat AF ablation, while persistent conduction blocks have been reported to be present in only 21% using conventional ablation setups (Huo et al, 2020). Therefore, index and repeat ablation procedures as well as ablation within healthy compared to impaired myocardium need to be distinguished when evaluating LI and CF dynamics: In our analysis, baseline LI was lower compared to previous results on index AF procedures, but LI correlated better with ΔLI compared to CF which is in line with published data (Szegedi et al, 2021;Ikenouchi et al, 2022;Solimene et al, 2022;Yasumoto et al, 2022). Furthermore, baseline LI was lower compared to blood pool LI in 45% of RFC applications, whereas an elevation of tissue baseline LI beyond blood pool LI was observed in index AF procedures (Solimene et al, 2022).…”
Section: Value Of Combined Force and Impedance Assessment During Repe...supporting
confidence: 90%
“…Several experimental and clinical studies have recently been published reporting experiences of combined CF and LI assessment during index AF ablation (Szegedi et al, 2021;Gutbrod et al, 2022;Solimene et al, 2022;Yasumoto et al, Frontiers in Physiology frontiersin.org 2022). Single-shot devices have seen increased usage for index AF ablations in recent years (Mulder et al, 2021).…”
Section: Value Of Combined Force and Impedance Assessment During Repe...mentioning
confidence: 99%
“…Te decrease in impedance during RFCA application is assumed to be the result of ion mobility [12,13]. Several studies have reported that the magnitude of the impedance drop predicts acute PVI [14][15][16]. An impedance drop of >15-18 ohm was found to be associated with an increased risk of SP occurrence [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Utility of combined local impedance and contact force during RF ablation of atrial fibrillation. ), http://links.lww.com/HCO/A93] [16,21 ▪▪ ,23 ▪ ].…”
Section: Combined Contact Force and Local Impedance Assessmentmentioning
confidence: 99%